“Becoming” a cooperative learner-teacher - Surian, Alessio; Damini, Marialuisa (Anales de Psicología / Annals of Psychology, 2014)
This paper presents an overview of the theoretical background concerning the challenges for secondary school teachers implementing cooperative learning in areas such as alternative student assessment technique, student’s resistance to collaborative techniques, planning and class management, teacher training, advancement, and evaluation. The research is based upon data gathered in the Italian Veneto and Emilia Romagna regions through focus groups with secondary school teachers. The educational project focuses on the use of critical incidents as training and educational tools with particular attention for cooperative learning approaches to transition situations and intercultural learning. It reviews different methodological options and explores ways to apply the critical incidents method in addressing the screening and development of intercultural competence within cooperative learning educational settings.